Review of the Evolution of Mining-Induced Stress and the Failure Characteristics of Surrounding Rock Based on Microseismic Tomography - Qiankun Zhu; Xingdong Zhao; Erik Westman (Shock and Vibration)
With the gradual depletion of shallow resources, deep mining has become an inevitable trend and has become an important part of the world mining industry. The high stress concentration caused by redistribution of original stress field will lead to stress-driven failure of surrounding rock; conventional methods, such as point-location stress measurement, analytical analysis, numerical simulation, and physical modeling, are not able to completely reflect the distribution and evolution characteristics of the mining-induced stress field in real time and at mine scale, so it is difficult to fully understand, control, and prevent mining-induced injuries and fatalities. In the past decades, microseismic monitoring technology, velocity tomography, numerical simulation, and laboratory test technology have been successfully applied to better understand mining-induced stress and rock mass failures. The combination of these methods has led to innovative ways to investigate the mining-induced stress field, surrounding rock failure, and hazard prevention. This review focuses on the mining-induced stress and velocity tomography based on microseismic monitoring data. Research progress in analysis and measurement methods of mining-induced stress, rock mechanics for mining, and velocity tomography practices are presented.